PARTISIPASI PEDAGANG DALAM MENJAGA KETERTIBAN PASAR KAGET MINGGU DI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Binsar "; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Binsar (1101136301), the participation of traders in maintaining order in the Kaget Minggu market in Tarai Bangun village district Tambang subdistrict Kampar 2016 guided by Drs.H.Zaili Rusli, M.siResearch on Merchant Participation In Keeping Order kaget minggu market in the tarai bangun District of kampar (2014-2016). The research was done in the kaget market that operates from eight to twelve o'clock. The formulation of the problem formulated in the formulation of the problem is How the participation of traders in the Kaget Minggu market to maintain order in the village Tarai Bangun?In this study, the authors used the descriptive method, which is done by analyzing the data and facts. This method as a process of solving problems examined by explaining the state of an object of research based on the facts available. To obtain the necessary data the authors made some observations on site Kaget Minggu market research, and interviews with relevant parties.The results showed that the market presence kaget minggu market greatly help society around housing were located far from the shopping center and the city center for shopping. Kaget minggu market presence not only facilitate local residents to shop for groceries or weekly, but the price of the goods sold are relatively cheaper, so that people find it easier and cheaper in the shop. However, the existence kaget minggu market also provides a negative impact on the environment as well as public order, as shanties irregular that cause congestion. To that end, the response of traders is needed so shocked the market well ordered and tidy. For those reasons, the Government of tarai bsngun village needed to steer traders who aim to control the kaget minggu market that is no longer a problem in the environment community.Keywords: Participation trader, controlling traders, market kaget